RING Finger Protein 38 Is a Neuronal Protein in the Brain of Nile Tilapia, Oreochromis niloticus - Cham, Kai Lin; Soga, Tomoko; Parhar, Ishwar S. (Frontiers in Neuroanatomy, 2017)
Really interesting new gene (RING) finger protein is a type of zinc - binding motif found in a large family of functionally distinct proteins. RING finger proteins are involved in diverse cellular processes which include apoptosis, DNA repair, cell cycle, signal transduction, tumour suppressor, vesicular transport and peroxisomal biogenesis. RING finger protein 38 (RNF38) is a member of the RING finger protein family whose function(s) still remains unknown. To gain insight into the putative, regional influence of RNF38 in the central nervous system, localization of its expression was sought. Therefore, the aim of this study was to identify the neuroanatomical location(s) of rnf38 mRNA and its peptide, type of RNF38-expressing cells, and levels of rnf38 gene expression in the brain of male tilapia. The distribution of rnf38 mRNA and its peptide was visualised using in situ hybridisation with digoxigenin-labelled RNA antisense and immunocytochemistry, respectively. Rnf38 mRNA and its peptide showed identical distribution throughout the brain which included the telencephalon, preoptic area, optic tectum, hypothalamus, cerebellum, and the hindbrain. Furthermore, double-labelling immunocytochemistry of RNF38 with neuronal marker HuC/D showed that majority of the RNF38 protein, although not all, were expressed in the nucleus of neurons. Quantitative real-time PCR showed the highest level of rnf38 mRNA in the midbrain, followed by preoptic area, cerebellum, optic tectum, telencephalon, hindbrain and hypothalamus. These findings show a differential spatial pattern of RNF38 in the brain of tilapia, which suggest its potentially diverse functions related to neuronal activity.